Analiza topografije papile vidnega živca pri zdravih osebah s Heidelbergovim tomografom mrežnice in z analizatorjem debeline mrežnice - Rekič, Andreja (Medicinski razgledi, 2005)
Optic nerve head topography analysis using the Heidelberg retina tomograph I (HRT) and the Retinal thickness analyzer (RTA) is important in the early diagnosis and follow up of glaucoma. The aims of our research were to obtain our own database for optic disc topography parameters in normal eyes using HRTand RTA, and assess reproducibility of measurements and clinical agreement between both devices. 50 healthy volunteers underwent HRT and RTA examinationsof both eyes. To determine reproducibility of measurements 10 volunteers repea ted the examinations of left eyes after a week. Differences between measurements by HRT and RTA were tested for statistical significance. Clinical agreement was assessed with limits of agreement and reproducibility with repeatability coefficient and intraclass correlation coefficient (ICC). Statistically significant differences (p 0.10 for cup area(0.15), rim area (0.19), maximum cup depth (0.13), height variation contour (0.11), and RNFL cross-sectional area (0.14) measured by RTA. ICC was good (> 90%) for most parameters, except for mean RNFL thickness (89%) measured by HRT and height variation contour (84%) measured by RTA. The two devices cannot be used interchangeably in clinical practice. At present, clinical usefulness of HRT is superior to RTA.
Keywords: Mrežnica; Retina; Optični disk; Anatomy And Histology; Optic Disk; Tomografija; Tomography; Srednja leta; Starostniki; Middle Age; oftalmologija; Aged; oko; anatomija; histologija